Solar Panel Energy Analysis on Remote Control Mobile Robots - Agus Ismangil; Syarif Hidayatulloh Hidayatulloh; Teguh Puja Negara; Syaeful Anwar (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2026)
The ever-increasing energy demand due to technological and industrial developments is driving the search for environmentally friendly energy solutions. Renewable energy, particularly solar energy, offers great potential to replace dependence on dwindling fossil fuels. As a manifestation of innovation in the field of robotics, this Android-based remote-controlled mobile robot is designed to use a 2WP monocrystalline solar panel as the main energy source, with a battery as additional power storage. This robot system integrates an Arduino Uno microcontroller for data processing and an HC-05 Bluetooth module that can control the robot remotely through an Android application. By utilizing solar energy through the solar panel, the robot can reduce dependence on conventional batteries, while increasing energy efficiency. Trials were conducted to evaluate system performance, including measuring the voltage, current, and efficiency of the solar panel. This research aims to contribute to the development of environmentally friendly robotics technology utilizing solar energy. The results of this study indicate that the designed system can work according to plan and has the potential for further development.